Non-cancer disease mortality and risk analysis among medical X-ray workers in China. (19th November 2009) - Wang, J.X.; Zhao, Y.C.; Jia, W.H.; Li, B.X.; Zhang, L.A.; Wang, Z.Q.; Fan, Y.G.; Zhang, J.Y.
The non-cancer disease mortality (1950-1995) among 27 011 medical diagnostic X-ray workers was compared to that of 25 782 other medical specialists employed between 1950 and 1980 to provide evidence of human non-cancer disease death produced by protracted and fractionated exposure to ionising radiation and assess the resultant non-cancer disease death risk. The total non-cancer disease mortality among the X-ray workers was significantly higher than mortality in the control group (RR = 1.2, 95% CI: 1.1-1.3). Significantly elevated risks were found for blood-forming system diseases (mainly from aplastic anaemia), circulatory system diseases (mainly from coronary heart disease and stroke) and nervous system diseases and the Relative Risks (RRs) were 3.7, 1.3 and 2.1, respectively. The pattern of risk associated with the duration of employment and the age and calendar year of initial employment suggest that the excess RR of blood-forming system diseases and coronary heart disease and stroke could be partly related to radiation exposure.